PENGARUH MULSA ORGANIK TERHADAP PERTUMBUHAN, PRODUKSI DAN EFISIENSI PENGGUNAAN AIR TANAMAN KEDELAI DENGAN PENGAIRAN SEPARUH DAERAH AKAR - Andi Bahrun .; La Ode Safuan -; Dedi Erawan; Fitri Saharia (Fakultas Pertanian Universitas Halu Oleo, 2014)
The objective of this research was to study the effect of organic mulch on growth, yield dan water use efficiency. The experiment was conducted in Kendari from August until September 2013. The experimental design was randomized complete block design with 3 replications and designed with a 4m x 1.2m plot size . The treatments were; (1) Fully root zone irrigation (FRI); (2) Partial root zone irrigation (PRI) without mulch; (3) PRI with mulch of dry thick leaf; (4) PRI with mulch of dry Chromolena shoot and (5) PRI with mulch of dry Imperata shoot. Irrigation was done every day at sowing time up to 26 days after sowing (DAS) but at 27 DAS up to 42 DAS, irrigation was done every two days. The results showed that the PRI with different organic mulch increased soil moisture and water use efficinecy (WUE), decreased soil temperature and maintained growth, shoot dry weight and seed yield of soybean. PRI with. dry thick leaf mulch and Imperata cilindrica mulch increased WUE , dry Chromolaena odorata shoot mulch and Imperata cilindrica shoot mulch increased WUE of soybean 40.94 % and 39.77 with seed yield increased 6,47% and 5,76%, respectively, compared with FRI without organic mulch. While, Chromolena odorata shoot mulch and PRI without organic mulch increased WUE 29.24% and 20.47% with seed yield decreased 2.19% and 8.86%, respectively compared with FRI without organic mulch. However, PRI with dry thick mulch, Chromolaena odorata shoot mulch and Imperata cilindrica shoot mulch increased WUE 16.99%, 7.28% and 16.02% with increased seed yield 16.54%, 7.09% and 15.75%, respectively, compared with PRI without mulch. Keywords: Chromolaena odorata, dry season, Imperata cilindrica, dry thick leaf, The objective of this research was to study the effect of organic mulch on growth, yield dan water use efficiency. The experiment was conducted in Kendari from August until September 2013. The experimental design was randomized complete block design with 3 replications and designed with a 4m x 1.2m plot size . The treatments were; (1) Fully root zone irrigation (FRI); (2) Partial root zone irrigation (PRI) without mulch; (3) PRI with mulch of dry thick leaf; (4) PRI with mulch of dry Chromolena shoot and (5) PRI with mulch of dry Imperata shoot. Irrigation was done every day at sowing time up to 26 days after sowing (DAS) but at 27 DAS up to 42 DAS, irrigation was done every two days. The results showed that the PRI with different organic mulch increased soil moisture and water use efficinecy (WUE), decreased soil temperature and maintained growth, shoot dry weight and seed yield of soybean. PRI with. dry thick leaf mulch and Imperata cilindrica mulch increased WUE , dry Chromolaena odorata shoot mulch and Imperata cilindrica shoot mulch increased WUE of soybean 40.94 % and 39.77 with seed yield increased 6,47% and 5,76%, respectively, compared with FRI without organic mulch. While, Chromolena odorata shoot mulch and PRI without organic mulch increased WUE 29.24% and 20.47% with seed yield decreased 2.19% and 8.86%, respectively compared with FRI without organic mulch. However, PRI with dry thick mulch, Chromolaena odorata shoot mulch and Imperata cilindrica shoot mulch increased WUE 16.99%, 7.28% and 16.02% with increased seed yield 16.54%, 7.09% and 15.75%, respectively, compared with PRI without mulch. Keywords: Chromolaena odorata, dry season, Imperata cilindrica, dry thick leaf,